Acoustic, volumetric and spectral studies of binary liquid mixtures of aliphatic dialkylamine and 2-alkanols at different temperatures. (May 2019) - Dubey, Gyan Prakash; Rani, Seema; Kumar, Harsh
Highlights: Binary mixtures containing amine with alkanol were investigated using volumetric, acoustic and spectral techniques. Various excess and deviation properties were computed. Interactions present between unlike molecules were discussed. Abstract: This article reports experimental densities ρ and speeds of sound ( u ) for the binary mixtures of di-n-butylamine and diisopropylamine with 2-butanol and 2-pentanol at a temperature range of (293.15–308.15) K with a temperature step of 5 K over entire composition range and at atmospheric pressure. Various thermodynamic parameters have been calculated using experimental data of densities and speeds of sound. The different parameters calculated are excess molar volume V m E, excess isentropic compressibilities κ s E, deviations in speed of sound u D, apparent molar volumes V ϕ, partial molar volumes V ¯ m, excess partial molar volumes V ¯ m E excess intermolecular free lengths L f E and excess acoustic impedance Z E . These parameters have been analysed in terms of nature and extent of intermolecular interactions. Effects of temperature, chain length and branching on intermolecular interactions have also been examined. Apart from this, FT-IR spectroscopy technique has also used to find more support for the results obtained from the calculated thermodynamic parameters. All the calculated properties have been correlated using Redlich-Kister type polynomial equation by the method of least-squares for the estimation of the binary coefficients and the standard deviations.